Implementation of Investment Facility Services in the Ministry of Investment - Rudito, R Bayu; Sutrisno, Edy; Karunia, R Luki (KnE Social Sciences, 2022)
This study aimed to examine the implementation of policies concerning the investment facility services of the Online Single Submission system (OSS) version 1.1 which was launched in January 2020. According to the results of a previous survey of facilities in 2020, there had been a decrease in the level of satisfaction concerning the effectiveness and efficiency of facility services, and also a decrease in the processing targets for the import facility services. The researchers of this study used a qualitative approach and collected data through interviews and document analysis. Edward’s theory was employed, which focuses on four aspects: communication, disposition, resources, and bureaucracy. This was combined with three perspectives of performance indicators from the Ministry of Investment/BKPM: customers, internal processes, and learning. The results indicated that the investment facility services of the OSS version 1.1 have not been effective due to several factors, including: (1) lack of communication and coordination, and policy inconsistencies; (2) unclear service information, and a lack of technical guidance and socialization; (3) a lack of support for resources through the budget, human resources and infrastructure; and (4) a lack of periodic structured evaluation. The recommendations are thus as follows: first, the government needs to make informative and detailed guidelines for facility services and conduct socialization with stakeholders before a policy is implemented. Second, there is a need for periodic internal evaluations every month; the results of the evaluation should be recorded; follow-up improvements should be made; and the obstacles found should be submitted to the Management Review Meeting. Third, the facility unit should detail its training needs and training should be carried out regularly to improve the capabilities of its employees. Fourth, the government needs to create a fully integrated facility service system, and when building this, it is necessary to apply the principles of clarity, convenience, acceleration, transparency, legality, and measurability. Keywords: communication, information, coordination, consistency, evaluation, socialization